Usage of Financial Services and Financial Performance of Agribusiness MSMEs in Greater Kigezi Sub-Region, Uganda - Kabagambe Jesse David; Moses agaba (International Journal of Management and Business Applied, 2026)
This study examines the influence of financial usage on the financial performance of agribusiness micro, small and medium enterprises (MSMEs) in Uganda’s Greater Kigezi sub-region. While financial inclusion initiatives in Uganda have significantly expanded access to formal financial services, emerging evidence suggests that access alone does not guarantee improved enterprise outcomes unless services are actively and consistently used. Rural agribusiness MSMEs, which operate in seasonal, cash-intensive, and infrastructure-constrained environments, provide an important context for evaluating whether financial usage translates into measurable performance gains. A cross-sectional survey design was employed, and primary data were collected from agribusiness MSME owners and managers across the six districts of Greater Kigezi. A total of 208 valid observations (N = 208) were analyzed using descriptive statistics, correlation analysis, and ordinary least squares (OLS) regression. Measurement quality was assessed prior to estimation. Content validity was confirmed (CVI = 0.90), while construct adequacy of the financial usage indicators was evaluated using the Kaiser–Meyer–Olkin (KMO) measure and Bartlett’s Test of Sphericity. The KMO value of 0.500 indicated marginal sampling adequacy, while Bartlett’s Test was statistically significant (χ² = 71.523, df = 1, p < .001), confirming the presence of meaningful correlations among the usage indicators. Given the behavioral and heterogeneous nature of usage, indicators were retained as observed measures rather than aggregated into a composite factor. Reliability diagnostics were satisfactory. Empirical results reveal a positive and statistically significant relationship between financial usage and MSME financial performance. The study concludes that deepening the actual use of financial services is critical for improving agribusiness MSME profitability and stability in rural Uganda and recommends that inclusion policies shift from access expansion toward usage-oriented interventions.